Amplitude Changes of the Electrically Evoked Compound Action Potential in Children with Cochlear Implants: Preliminary Results - Pourjavid, Alireza (Tehran University of Medical Sciences, 2011)
OBJECTIVE: Use of electrical instead of acoustical stimulation has made much objective electrophysiological evaluation possible. This is useful for management process of young children before and after the cochlear implant. These evaluations have been used for assessment of neuronal survival before cochlear implant and for monitoring of prosthesis function during and after the surgery. Electrically evoked compound action potential is one of these tests which makes a valid and reliable objective evaluation possible. The aim of this study was to evaluate the potential's amplitude changes three months after receiving the device in pediatric cochlear implant recipients. METHODS: In this longitudinal study, changes of the potential's amplitude in four given electrodes in four sessions after receiving the device are evaluated by approximately one month intervals in children implanted in Amir Alam and Hazrat-e-Rasoul hospitals, Tehran in July to December 2007. FINDINGS: The mean amplitude of the electrodes did not significantly change in different sessions, while there was significant difference between the first and the other electrodes’ responses in every session (P<0.05). CONCLUSION: Due to high reliability of the responses, the clinician can fit the speech processor for a long time. Better responses in apical electrodes may lead to develop an effective coding strategy.